EIRLSBN : (IRRI, International Rice Research Institute, 2013)
Considerable progress has been made in the development of new varieties of rice in eastern India, although the literature on this subject is limited. Evidence of this is the development and release of many new improved varieties. At least 20 of these varieties have been released in India from lowland dryland transport Network Breeding Oriental (EIRLSBN).